Novel synthetic amino acid copolymers that inhibit autoantigen-specific T cell responses and suppress experimental autoimmune encephalomyelitis. - Fridkis-Hareli, M; Santambrogio, L; Stern, J; Fugger, L; Brosnan, C; Strominger, J (2002)
Copolymer 1 (Cop 1, Copaxone [Teva Marion Partners, Kansas City, Missouri, USA]), a random amino acid copolymer of tyrosine (Y), glutamic acid (E), alanine (A), and lysine (K), reduces the frequency of relapses by 30% in relapsing-remitting multiple sclerosis (MS) patients. In the present study, novel random four-amino acid copolymers, whose design was based on the nature of the anchor residues of the immunodominant epitope of myelin basic protein (MBP) 85-99 and of the binding pockets of MS-associated HLA-DR2 (DRB1*1501), have been synthesized by solid-phase chemistry. Poly (Y, F, A, K) (YFAK) inhibited binding of the biotinylated MBP 86-100 epitope to HLA-DR2 molecules more efficiently than did either unlabeled MBP 85-99 or any other copolymer including Cop 1. Moreover, YFAK and poly (F, A, K) (FAK) were much more effective than Cop 1 in inhibition of MBP 85-99-specific HLA-DR2-restricted T cell clones. Most importantly, these novel copolymers suppressed experimental autoimmune encephalomyelitis, induced in the susceptible SJL/J (H-2(s)) strain of mice with the encephalitogenic epitope PLP 139-151, more efficiently than did Cop 1. Thus, random synthetic copolymers designed according to the binding motif of the human immunodominant epitope MBP 85-99 and the binding pockets of HLA-DR2 might be more beneficial than Cop 1 in treatment of MS.